Living with COVID-19 in the community during the first wave of the pandemic: Lessons from patients for healthcare providers and policy makers - Linda Rozmovits; Michelle Marcinow; Ilja Ormel; Terence Tang; Elizabeth Mansfield; Kerry Kuluski; Seema Marwaha; Susan Law (The Beryl Institute, 2023)
This qualitative descriptive study explores patients' experiences of living with COVID-19, in the community, during the early stages of the pandemic. Between October 2020 and April 2021, fifteen semi-structured, video-recorded interviews were conducted, via Zoom, with participants in five Canadian provinces. Participants self-identified as having had a confirmed or suspected case of COVID-19. The constant comparative method was used to produce a thematic analysis of findings. Key findings include 1) PCR tests were not widely available in Canada, during the first wave, so many participants lacked a confirmed diagnosis and, subsequently, encountered challenges accessing specialist medical care; 2) Rapidly changing protocols around testing also impacted return to work as employers' requirements were sometimes misaligned with public health guidelines; 3) Participants often found public health measures to be illogical, inconsistent, or sub-optimally implemented, and frequently perceived them as politically motivated rather than evidence-based; 4) some individuals with persistent symptoms had difficulty gaining acknowledgement and support for what is now more widely acknowledged to be long-COVID; and 5) The view that healthcare providers need a more nuanced approach to patients who lack a confirmed diagnosis or present with hard-to-explain symptoms was widely shared. There is the need for greater responsiveness to the lived experiences of patients with COVID-19, especially those with persistent symptoms, in developing clinical pathways and social supports. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Policy%20%26%20Measurement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.